Penerapan Terapi Musik Campursari pada Pasien Halusinasi Pendengaran Di RSJ Grhasia Yogyakarta: Terapi Musik Campursari pada Pasien Halusinasi - Sarka Ade Susana; Abdul Ghofur; Defito Kusuma Wardhana (Poltekkes Kemenkes Kupang, 2026)
Auditory hallucinations are a major problem in schizophrenic patients requiring appropriate non-pharmacological management. Objective: To describe the implementation of nursing care for two patients with auditory hallucination sensory perception disorders at Wisma Nakula Sadewa, Grhasia Mental Hospital Yogyakarta, and to compare both patients' responses to campursari music therapy. Method: Case study of two adult male patients diagnosed with schizophrenia. Data were collected through observation, interviews, and medical record review. Hallucinations were measured using AHRS (Auditory Hallucinations Rating Scale). Interventions were conducted in three sessions of 40 minutes each, including 15 minutes of music listening. Results: Both patients experienced auditory hallucinations with a history of relapse due to medication non-compliance. After three campursari music therapy sessions, Mr. SW's AHRS score decreased from 27 (severe) to 22 (moderate) and Mr. P's from 33 (severe) to 25 (moderate). Both patients reported feeling calmer and reduced hallucinations. Conclusion: The application of campursari music therapy in nursing care proved effective in reducing AHRS scores in patients with auditory hallucination sensory perception disorders.